Theoretical investigation of the solubilization of COOH-functionalized single wall carbon nanotubes in water - Mananghaya, Michael (Animo Repository, 2016)
The paper discusses the impact of functionalization in understanding the solubility of (n, 0) single walled carbon nanotube (SWCNT) with varying diameters (n = 8-16) to increase its dispersion in water with the aide of spin-unrestricted density functional theory (DFT). A finite nanotube model saturated with hydrogen at both ends was functionalized with a carboxylic acid at the sidewall. Functionalization resulted in an enhancement in the solubility of the nanotubes in water which can be explained by the increase in dipole moment as visualized in the HOMO-LUMO surface plots. This behavior depends on the tube diameter marked with saw tooth like periodic features which originated from their different π bonding structures manifested in the electronic band gaps. Furthermore, as the degree of sidewall functionalization increases, the SWCNT sample becomes more soluble as assessed by the calculated Gibbs free energies of solvation. © 2016 Elsevier B.V.